Adult Cochlear Implant Users Are Able to Discriminate Basic Tonal Features in Musical Patterns: Evidence From Event-related Potentials. Issue 9 (October 2016) - Hahne, Anja; Mainka, Alexander; Leuner, Annegret; Mürbe, Dirk
Abstract : Objective: Measurement of electrophysiological correlates of discrimination abilities of basic musical features in pre- and postlingually deafened adult cochlear implant (CI) users. Study Design: Electroencephalographic study. Comparison between CI users and matched normal hearing controls. Patients: Thirty-six hearing impaired adults using a cochlear implant for 4 to 15 months. Profound hearing impairment was acquired either before (N = 12) or after language acquisition (N = 17). Seven patients suffered from a single-sided deafness. Methods: Presentation of auditory stimuli consisting of musical four tone standard patterns and deviant patterns varying with regard to tone pitch, timbre, intensity, and rhythm of two different degrees. Analysis of electrophysiological, event-related mismatch responses. Results: Cochlear implant users elicited significant mismatch responses on most deviant features. Comparison to controls revealed significantly smaller mismatch negativity amplitudes. Except for one parameter (pitch) there were no reliable differences between pre- and postlingually deafened CI users. Conclusion: Despite a highly reduced complexity of neural auditory stimulation by the cochlear implant device in comparison to the physiological cochlear input, CI users exhibit cortical discriminatory responses to relatively subtle basic tonal alterations.